Teaching Exodus as “Problem Text” - Mathews McGinnis, Claire (Teaching theology and religion, 2002)
This essay explores how one might use the “problem” of the hardening of Pharaoh's heart as a learning opportunity in the classroom. The author identifies two pedagogical aims: (1) cultivating more sophisticated, critical readers of the Bible; and (2) helping students reflect on the contextual nature of interpretation. The essay discusses in some detail various ways of teaching the text, including an exercise in close reading, examination of sources, and a selective study of the history of interpretation. It also explores various lessons to be learned from these exercises, and addresses applicability of the approaches to other teaching contexts. An earlier version of this paper was prepared for the “Problem Texts” group of the consultation “Teaching the Bible in the 21st Century,” held at the Wabash Center in Crawfordsville, Indiana.